2018
DOI: 10.5530/srp.2019.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Drug Availability and Influencing Factors in Several Low, Lower and Upper- Middle Countries: A Systematic Review

Abstract: Drugs are vital to saving and improving public health. However, medicines are often not available at the facility because stocks run out or in particular, pharmaceuticals are not available due to a shortage of supplies. Implementation of pharmacy services should ensure safe, quality, usable and affordable availability drug. A systematic review was conducted to identify related studies. Electronic databases used to identify relevant studies are, ScienceDirect, Plos, PubMed and Google Scholar. This study is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…33 The study found that price has the same impact on the availability of essential medicines in Africa as it did in Asian poor countries. 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 The study found that price has the same impact on the availability of essential medicines in Africa as it did in Asian poor countries. 6 …”
Section: Discussionmentioning
confidence: 99%
“…This effect can be seen in Ethiopia and Malawi, where a lack of cooperation between government and non-governmental organizations in providing access to essential medicines has a significant impact on accessibility. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, os altos preços dos medicamentos tornam os medicamentos inacessíveis para muitas pessoas (26) . A disponibilidade de medicamentos nos países em desenvolvimento ainda precisa ser melhorada, aumentando o acesso a medicamentos e controlando os preços, usando políticas governamentais apropriadas (27) . Por outro lado, investir em inovação e na produção de novos medicamentos sem que os mesmos sejam acessíveis é favorecer o comércio, o lucro desmedido e, em certas ocasiões, até extorsivo, em detrimento da saúde e dos princípios que regem o direito à vida com dignidade (28) .…”
Section: Discussionunclassified
“…The availability of drugs in low, lower and upper middle countries still need to be improved by increasing drug access and enhancing prices by using appropriate government policies. 34…”
Section: Essential Medicines Conceptmentioning
confidence: 99%